2021
DOI: 10.5334/bc.162
|View full text |Cite
|
Sign up to set email alerts
|

Survey study on energy use in UK homes during Covid-19

Abstract: To contain the spread of Covid-19, governments across the world imposed partial or complete lockdowns. National energy demand decreased in periods of lockdowns; however, as people spent more time at home, residential energy use likely increased. This paper reports the results of a UK survey study (N = 1016 participants) about their energy-use practices during the first lockdown in March 2020. The results indicated that self-reported heating behaviours did not substantially change during lockdown. Regarding app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 19 publications
6
22
0
Order By: Relevance
“…These approaches removed the initial (pre-lockdown) effects of the pandemic from the control group but ignored weather fluctuations between years. Analysing ECMWF weather data showed that in GB the weather during the first lockdown was unseasonably warm and sunny, and the combination of temperature and solar irradiance was unlike any period in the previous 18 months [21].…”
Section: Methods For Estimating the Changes In Total Energy Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches removed the initial (pre-lockdown) effects of the pandemic from the control group but ignored weather fluctuations between years. Analysing ECMWF weather data showed that in GB the weather during the first lockdown was unseasonably warm and sunny, and the combination of temperature and solar irradiance was unlike any period in the previous 18 months [21].…”
Section: Methods For Estimating the Changes In Total Energy Consumptionmentioning
confidence: 99%
“…Studies on the impact of the first lockdown applied simple methods which, while able to deliver results quickly, were unable to account for different weather conditions during lockdown 1 compared with the preceding weeks or the same period in the previous year. Weather is known to be a significant driver of domestic electricity and gas demand [27], and the weather conditions were unusual during lockdown 1 [21]. The most robust UK study of this period [5] was limited to a sample of 280 social housing properties in Cornwall, mostly with a retired or non-working household member.…”
Section: Aims and Paper Outlinementioning
confidence: 99%
“…Information on length of heating is not available for the majority of SERL Observatory participants. However, Huebner et al (2021) reported on the responses of 1,016 participants who took part in the SERL Covid-19 survey, these participants were drawn from the SERL Observatory participants who had been recruited by September 2019. Huebner et al found a mean of 7.5 heating hours during the first lockdown and that less than 15% of respondents reported increasing their heating hours during the first lockdown.…”
Section: Table 4 Regression Coefficients Confidence Intervals and P V...mentioning
confidence: 99%
“…Therefore, an increase in water bills might indicate an increase in consumption. Moreover, similar studies successfully used online surveys to understand the impact of COVID-19 lockdown on water and energy use [39,61].…”
Section: Bias and Limitationmentioning
confidence: 99%